The Implementation of Mnemonic Method to Improve the Primary School Learner’s English Writing Skills - Jamik, Haritzah Ningrum; Soeharno, Soeharno (Journal of Primary Education, 2020)
The problems of this research were the learners’ difficulties to express their ideas into a simple English sentence. The learner low motivation while learning English was also one of the influential factors. This research aims to find out how mnemonic method could improve the learners’ writing skills in the primary school during learning English. The subjects consisted of fifth graders of Integrated Islamic 5 Primary School, Semarang. The applied method in this research was quasi experimental research. The findings showed the learners’ writing skills were improved after being intervened by the mnemonic method. The learners were motivated and were not afraid to express the ideas into simple sentences. The writing skill in experimental class obtained better than that of the conventional class as well as than learning achievements. The post-test results showed the learners’ scores were higher than the standard after being intervened by mnemonic method. It was 80. It could be concluded that the mnemonic could improve the learners’ skills to write the simple English sentences.